CERKIS: Big Book Learning Media Based on Quiz Stories for Second-Grade Elementary Schools - Putri, Ni Made Sinta Ariayu; Yudiana, Kadek; Trisna , Gusti Ayu Putu Sukma (Mimbar Ilmu, 2024)
Teachers strive to recognize and develop students' potential through the learning process. However, deficiencies are often found in the process, such as learning feeling monotonous. One of the causes is the need for more variety in learning media. The observations in the field show the need to develop learning media for Indonesian language subjects, especially for students who cannot read and tend to focus on pictures. This research aims to develop Big Book learning media based on quiz stories on health care material for class II elementary schools. This research is a development research type with the ADDIE model. The research subject is a big book learning media based on quiz stories on health care material. Data collection used observation, interview, and questionnaire methods. Data was analyzed qualitatively from the results of expert reviews and quantitatively from scores in the form of test results. The research results showed that material experts scored 0.98, learning design experts 0.97, and media experts 0.97. The results of the practicality test of student responses through individual trials were 95.11%; The teacher response test was 93.75%, so it was concluded that the development of big book learning media based on quiz stories was very valid and practically applied to Indonesian language content on maintaining health in class II elementary schools. This research has theoretical and practical implications in that the big book learning media based on developed quiz stories could solve the problem of students' low/low reading ability.